Insulated Wire
Patent Information
- Application Number
- JP2023550119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-04
- Filing Date
- 2022-02-21
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2042-02-21
AI Technical Summary
Existing magnet wires require adhesive layers between thermoplastic insulators and conductors for adequate adhesion, leading to potential delamination and increased thickness, which affects flexibility and electrical performance, especially at high temperatures and in square/rectangular shapes.
A magnet wire with a thermoplastic insulation layer composed of polyaryletherketone polymer and talc, directly applied to the conductor without an adhesive layer, ensuring strong adhesion and flexibility through controlled melt viscosity and surface treatments.
The solution provides improved adhesion and flexibility, reducing delamination and maintaining electrical integrity at high temperatures, while eliminating the need for adhesive layers, thus enhancing wire performance in electric vehicles.
Smart Images

Figure 2022175515000001 
Figure 2022175515000002 
Figure 2022175515000003
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 152009, filed February 22, 2021, and European Patent Application No. 21171941.4, filed May 4, 2021, the contents of which are incorporated herein by reference in their entirety for all purposes. In the event of any discrepancy affecting the clarity of terminology or wording between this application and this PCT application, reference shall be made solely to this application.
[0002] The present invention relates to wires, especially magnet wires, containing a thermoplastic insulation, in particular to wires containing a thermoplastic insulation of a polyaryletheretherketone composition without any adhesive layer. [Background technology]
[0003] Magnet wire is increasingly being used in electric vehicles, for example, as it is present in inverter drive motors, motor starter generators, transformers, etc. Typically, magnet wire is made by applying electrical insulation to a metal conductor, such as copper, aluminum, or alloy conductors. The insulation provides electrical integrity and prevents shorting of the magnet wire. Conventional insulation often consists of a polymer enamel film that is applied as successive layers and fired in an oven. To achieve higher withstand voltage and partial discharge performance to meet increasing standards of electrical performance, it is typically necessary to apply more layers and therefore thicken the enamel. However, each successive pass through the firing oven reduces the adhesion between the enamel and the conductor, and it is difficult to form the enamel thickness outside of a certain range. Furthermore, increased stratification of the enamel can result in solvent blistering or beading and / or reduced flexibility.
[0004] Recently, there have been attempts to form magnet wire insulation from extruded thermoplastic materials. The thermoplastic insulation is extruded over either bare conductors or conductors having an enamel insulation. For example, U.S. Patent No. 9,224,523 describes magnet wire in which polyetheretherketone ("PEEK") is extruded over an enamel layer. Similarly, U.S. Patent No. 9,324,476 describes magnet wire in which either PEEK or polyaryletherketone is extruded over an enamel layer.
[0005] EP 3642283 (WO 2018 / 234116) discloses a layered structure including a polymer layer and a varnish layer. There is no disclosure of a composition having the melt viscosity in the claimed range.
[0006] EP 0182580 discloses a polymer composition comprising a composition of polyaryletherketone and talc. There is no disclosure of a wire in which the composition is in direct contact with a conductor.
[0007] WO 2014 / 085083 discloses an insulating layer with PEEK. There is no disclosure of the filler ratio.
[0008] EP 2900470 (WO 2014 / 052801) does not disclose any claimed viscosities.
[0009] WO 2016 / 120592 discloses an insulating layer but does not disclose the subject matter of claim 1.
[0010] [Problem to be solved by the invention] When relatively high performance thermoplastic polymers are used, an adhesive layer is often required between the thermoplastic insulation and the conductor or underlying enamel layer to provide adequate interlayer adhesion. Thus, there is the potential for improved insulated magnet wires, and more particularly, improved magnet wires that include thermoplastic insulation without any adhesive layer and / or enamel layer.
[0011] The magnet wire must be sufficiently flexible to ensure good windability.
[0012] Furthermore, the adhesion between the insulating film and the conductor must be sufficient, especially when the wire is subjected to processes such as bending and stretching, which are likely to cause delamination between the insulating film and the conductor. If this delamination causes a void between the conductor and the insulating film, the electric field will concentrate there and cause dielectric breakdown, or the stress will concentrate there and the insulating film will tend to break easily.
[0013] Because of this improvement in the power output of electric vehicle motors, the amount of heat generated tends to increase, causing the temperature of the motor to rise, and therefore adhesion needs to be maintained at elevated temperatures.
[0014] Thus, there is a need for a wire that combines good windability with strong adhesion, especially after processing of the wire and at elevated temperatures.
[0015] Further problems may arise with square or rectangular shaped wires: indeed, the stresses on the corners and edges may be greater on these wires than on round wires, and it may be difficult to obtain the same thickness of insulation on all four sides and corners.
[0016] Using the composition disclosed in this invention, magnet wires aim to solve these technical problems.
[0017] BRIEF SUMMARY OF THE INVETION The invention is set out in the attached set of claims. The object of the invention is therefore a wire as defined in claims 1 to 45.
[0018] Another object of the invention is a method for manufacturing a wire as defined in any one of claims 46 to 48.
[0019] Another object of the invention is an electric machine or a stator as defined in claims 49 and 50.
[0020] Another object of the invention is the use as defined in claim 51.
[0021] Another object is an electric machine comprising at least one wire according to the invention.
[0022] More precise details and details regarding these objectives are provided below. Summary of the Invention
[0023] The wire of the present invention is - a conductor; at least one insulating layer formed around and in direct contact with the conductor, wherein the insulating layer comprises or is made of a composition comprising at least one polyaryletherketone polymer and 6 to 40% by weight of talc, based on the total weight of the composition, and the composition is heated at 400° C. and 1000 s. -1 At least 120 Pa when measured in accordance with ASTM D3835 . It has a melt viscosity of .s.
[0024] Thus, the insulating layer used in the context of the present invention can comprise a composition comprising the polyaryletherketone polymer disclosed in the present invention and talc, and the insulating layer used can be manufactured from a composition comprising the polyaryletherketone polymer disclosed in the present invention and talc.
[0025] It has been found that use of the above defined composition eliminates the need for adhesives, enamels or accelerators between the conductor and the thermoplastic insulation layer.
[0026] The insulating layer may be formed directly around the conductor. In some embodiments, one or more insulating layers may be formed around the conductor.
[0027] In another embodiment, the conductor may include a surface treatment, with the proviso that the surface treatment does not include any adhesive thermoplastic or thermosetting polymer. The surface treatment is more particularly selected from flame treatment, mechanical abrasion (e.g., shot blasting) and chemical treatment (e.g., etching). The surface is treated to modify the surface prior to application of the insulating layer. The surface is treated to chemically modify the surface and / or to change the surface condition.
[0028] At least one insulating layer can be formed by extruding the composition around the conductor. In certain embodiments, the composition can be extruded directly around the conductor.
[0029] In some embodiments, the wire is a magnet wire.
[0030] composition Details and embodiments relating to the composition polyaryletherketone polymer / talc are provided herein. The proportions of the components of the composition are given in weight percent and are based on the total weight of the composition.
[0031] The composition comprises at least one polyaryletherketone polymer and 6.0-40.0 wt.% talc based on the total weight of the composition.The composition comprises 6-40 wt.% talc based on the total weight of the composition.
[0032] As described in more detail below, the composition comprises: - at least one PAEK polymer, - 6.0 to 40.0% by weight of talc; - optionally at least one PAES polymer, - optionally at least one nucleating agent, - optionally comprising or consisting of at least one plastics additive;
[0033] First embodiment According to this first embodiment, the proportion of talc is at least 10.0% by weight. The composition preferably comprises at least 11% and / or at most 30% by weight, preferably at most 28% by weight, of talc relative to the total weight of the composition.
[0034] The proportion of talc is advantageously at least 11.0% by weight, further at least 11.5% by weight, further at least 12.0% by weight, further at least 12.5% by weight, further at least 13.0% by weight, further at least 13.5% by weight, further at least 14.0% by weight, further at least 14.5% by weight, further at least 15.0% by weight.
[0035] The proportion of talc is advantageously at most 30.0% by weight, further at most 29.5% by weight, further at most 29.0% by weight, further at most 28.5% by weight, further at most 28.0% by weight, further at most 27.5% by weight, further at most 27.0% by weight, further at most 26.5% by weight, further at most 26.0% by weight, further at most 25.5% by weight, further at most 25.0% by weight.
[0036] Compositions containing 10.0 to 26.0 weight percent talc have been found to provide good adhesion to conductors.
[0037] Second embodiment According to this second embodiment, the proportion of talc is between 5.0 and 10.0% by weight.
[0038] The proportion of talc is advantageously at least 5.5% by weight, even at least 6.0% by weight and even at least 6.5% by weight.
[0039] The proportion of talc is advantageously at most 9.5% by weight, further at most 9.0% by weight, further at most 8.5% by weight, further at most 8.0% by weight, further at most 7.5% by weight, further at most 7.0% by weight.
[0040] It has been found that compositions containing 5.5 to 9.5 wt.%, further 6.0 to 9.0 wt.%, and further 6.3 to 8.5 wt.% talc exhibit a good compromise of properties, in particular good adhesion to the conductor and good elongation at break.
[0041] The composition of the insulating layer may comprise or be made from only one PAEK polymer.
[0042] The composition of the insulating layer may also include or be made from two or more PAEK polymers. The PAEK polymers in the composition may be selected from the repeating units (R PAEK ) or they may differ in terms of molecular weight, i.e. melt viscosity.
[0043] Also, a composition may comprise or be made from one PAEK polymer and a polymer of a different nature.
[0044] More details about the components of the composition are provided herein.
[0045] PAEK Polymer The composition comprises or is made from at least one polyaryletherketone polymer, hereinafter referred to as a "PAEK polymer." As used herein, the term "PAEK polymer" refers to a polymer having repeating units (R 1 ) having Ar-C(═O)-Ar′ groups, where Ar and Ar′ are equal or different and are aromatic groups. PAEK ) means any polymer that contains at least 50% by weight of
[0046] In some embodiments, the PAEK polymer is at least 60% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, or at least 98% by weight of repeat units (R PAEK) having a repeating unit (R PAEK ) is represented by the following formulas (JA) to (JQ): [ka] [ka] [ka] (In the formula, each R' is equal to or different from one another and is selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine and quaternary ammonium; - j' is zero or an integer from 0 to 4, and j' is preferably 0.
[0047] In some embodiments, the repeating unit (R PAEK Each phenylene moiety in R' can independently have a 1,2-, 1,4-, or 1,3-bond to another moiety in the repeat unit that is different from R'. In some embodiments, the phenylene moieties have a 1,3- or 1,4-bond. In further embodiments, the phenylene moieties have a 1,4-bond.
[0048] Further, in some embodiments, the repeat unit (R PAEK j' in each occurrence of the repeat unit (R) can be zero; that is, the phenylene moiety does not have any substituents other than those that allow for attachment in the backbone of the polymer. In some such embodiments, the repeat unit (R PAEK ) is expressed by the following formulas (J'-A)~(J'-O): [ka] [ka] The compound can be represented by a formula selected from the group:
[0049] The PAEK polymer may be a homopolymer, random, alternating or block copolymer. When the PAEK polymer is a copolymer, it comprises repeat units (R PAEK ), or (ii) one or more repeating units of formulae (JA) to (JO) (R PAEK ) and repeating unit (R PAEK ) with a repeating unit (R* PAEK ) may be contained.
[0050] According to some embodiments, the repeat unit (R PAEK ) is the unit of formula (J'-A) to (J'-D): [ka] is selected from the group consisting of:
[0051] PAEKs are prepared by polycondensation techniques known in the art, especially by nucleophilic or electrophilic routes. More precisely, PAEKs can be prepared by aromatic nucleophilic substitution resulting in diaryl ether bonds. Polycondensation is generally carried out in a solvent such as diphenylsulfone at 300° C. or higher with the aid of a base such as K2CO3. More specifically, PAEKs can also be obtained by polycondensation of a mixture of at least one aromatic compound having two hydroxyl groups and at least one aromatic compound having two halogens, such as fluorine. For example, PEEK is generally prepared by reacting hydroquinone with 4,4'-difluorobenzophenone in diphenylsulfone in the presence of at least one alkali metal carbonate under an inert atmosphere at high temperatures, for example >300° C. Details on polycondensation involving nucleophilic substitution can be found, for example, in U.S. Pat. No. 4,176,222.
[0052] More precisely, PAEKs can be prepared by Friedel-Crafts electrophilic substitution, which results in diaryl ketone bonds. Polycondensation is generally carried out in a solvent at a temperature below 150° C. with the aid of a Lewis acid such as AlCl3. Details on polycondensation involving Friedel-Crafts electrophilic substitution can be found, for example, in U.S. Pat. No. 4,841,013, U.S. Pat. No. 4,816,556, WO 2011 / 004164 and WO 2014 / 013202.
[0053] PEEK The PAEK polymer in the composition may more specifically be a polyetheretherketone ("PEEK") polymer. As used herein, the term "PEEK polymer" refers to a polymer in which at least 50% by weight of the repeat units are of the formula J'-A (R PAEK ) means any polymer in which the repeat units of the PEEK polymer are of formula J'-A. In some embodiments, at least 75%, at least 85%, at least 95%, or at least 99% by weight of the repeat units of the PEEK polymer are of formula J'-A. In some embodiments, 99.99% by weight of the PEEK polymer are of formula J'-A. In some embodiments, substantially all of the repeat units of the PEEK polymer are of formula J'-A.
[0054] PAEK polymers can be prepared by any method known in the art for the production of polyaryletherketone polymers, see above. Additionally, PEEK is commercially available as KetaSpire® polyetheretherketone from Solvay Specialty Polymers USA, LLC.
[0055] As noted above, the composition may include or be made from two or more PAEK polymers. For example, the PAEK polymer may be aged at 400° C. for 1,000 s. -1The results may correspond to a combination of two PEEKs (PEEK1 and PEEK2) that differ in their melt viscosity as measured using a capillary rheometer with a die having dimensions of 0.5 mm diameter by 3.175 mm length according to ASTM D3835 at a shear rate of 100 Hz.
[0056] In some embodiments, at least 75%, at least 85%, at least 95%, or at least 99% by weight of the repeat units of PEEK1 and PEEK2 are repeat units of formula J'-A. In some embodiments, 99.99% by weight of PEEK1 and PEEK2 are repeat units of formula J'-A. In some embodiments, substantially all of the repeat units of PEEK1 and PEEK2 are of formula J'-A.
[0057] More particularly, PEEK1 can exhibit a viscosity (at the above conditions) of more than 300 Pas. The viscosity of PEEK1 can be 350-600 Pas. An example of a suitable PEEK1 is 380-500 Pas. . The polymer used is KetaSpire® KT-820 high viscosity grade PEEK having a melt viscosity of 100 .mu.s.
[0058] More particularly, PEEK2 may exhibit a viscosity (at the above conditions) of less than 200 Pas. The viscosity of PEEK2 may be between 100 and 200 Pas. An example of a suitable PEEK2 is 120 to 180 Pas. . The polymer used is KetaSpire® KT-880 high viscosity grade PEEK having a melt viscosity of 100 .mu.s.
[0059] The weight ratio PEEK1 / PEEK2 can be between 50 / 50 and 70 / 30, and even between 60 / 40 and 70 / 30.
[0060] Composition PAEK / PAES In an alternative embodiment, the composition may comprise one PAEK polymer and a polymer of different nature. In an advantageous aspect of this embodiment, the composition may comprise at least one PAEK polymer and at least one polyarylethersulfone polymer, hereafter "PAES polymer". The term "PAES polymer" refers to a polymer in which at least 50 mol % of the repeating units have the formula: [ka] (In the formula, - Each R 3 are equal to or different from each other and are independently selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium; - each c is equal to or different from one another and is independently selected from 0, 1, 2, 3, and 4, preferably 0; - T is a bond, a sulfone group [-S(=O) 2- ], and the group -C(R 4 )(R 5 )-(where R 4 and R 5 are equal to or different from each other and are selected from the group consisting of hydrogen, halogen, alkyl, alkenyl, alkynyl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine, and quaternary ammonium). PAES ) R 4 and R 5 is preferably a methyl group.
[0061] Preferably, the repeating unit (R PAES) are at least 60 mol %, 70 mol %, 80 mol %, 90 mol %, 95 mol %, 99 mol % of repeat units of formula (B).
[0062] PAES polymers are prepared by polycondensation techniques known in the art, particularly nucleophilic routes involving optionally substituted 4,4'-dihalodiphenyl sulfones, particularly optionally substituted 4,4'-dichlorodiphenyl sulfone.
[0063] In some embodiments, the PAES is polyphenylsulfone (PPSU). As used herein, "polyphenylsulfone (PPSU)" refers to a PAES having a repeating unit (R PAES ) are of the formula: [ka] (In the formula, R 6 and d in each case, respectively, R 3 and c are independently selected from the group described above for c. Preferably, each d in formula (B-1) is zero.
[0064] Preferably, the repeating unit (R PAES At least 60 mol %, 70 mol %, 80 mol %, 90 mol %, 95 mol %, or 99 mol % of the repeating units of formula (B-1) are repeating units of formula (B-2).
[0065] PPSU can be prepared by known methods and is available as RADEL® PPSU from Solvay Specialty Polymers USA, LLC.
[0066] PPSU suitable for use in the present invention may have a melt flow rate (MFR) in the range of 5.0 to 45.0 g / 10 min, preferably 10.0 to 40.0 g / 10 min, more preferably 15.0 to 35.0 g / 10 min, and even more preferably 20.0 to 30.0 g / 10 min, as measured according to ASTM D1238 using a temperature of 365° C. and a weight of 5.0 kg.
[0067] In some embodiments, the PAES is polyethersulfone (PES). As used herein, "polyethersulfone (PES)" refers to a PAES having a repeating unit (R PAES ) are more than 50 mol % of the formula: [ka] (In the formula, each R 7 and e in each case, respectively, R 3 and c are independently selected from the group described above for e. Preferably, each e in formula (B-2) is zero.
[0068] Preferably, the repeating unit (R PAES At least 60 mol %, 70 mol %, 80 mol %, 90 mol %, 95 mol %, or 99 mol % of the repeating units of formula (B-2) are repeating units of formula (B-3).
[0069] PES can be prepared by known methods and is available as VERADEL® PESU from Solvay Specialty Polymers USA, LLC.
[0070] PES suitable for use in the present invention may have a melt flow rate (MFR) in the range of 10.0 to 50.0 g / 10 min, preferably 15.0 to 45.0 g / 10 min, more preferably 20.0 to 40.0 g / 10 min, and even more preferably 25.0 to 35.0 g / 10 min, as measured according to ASTM D1238 using a temperature of 380° C. and a weight of 2.16 kg.
[0071] In some embodiments, the PAES is a polysulfone (PSU). As used herein, "polysulfone (PSU)" refers to a PAES having a repeat unit (R PAES ) are of the formula: [ka] (In the formula, each R 8 and f in each case, respectively, R 3 and c are independently selected from the group described above for a. Preferably, each f in formula (B-3) is zero.
[0072] Preferably, the repeating unit (R PAES At least 60 mol %, 70 mol %, 80 mol %, 90 mol %, 95 mol %, or 99 mol % of the repeating units of formula (B-3) are repeating units of formula (B-4).
[0073] PSU can be prepared by known methods and is available as UDEL® PSU from Solvay Specialty Polymers USA, LLC.
[0074] Preferably, the PAES is selected from the group consisting of PSU, PPSU, and combinations thereof. In some embodiments, the PAES includes PSU and PPSU. Most preferably, the PAES is PPSU.
[0075] PSU suitable for use in the present invention may have a melt flow rate (MFR) in the range of 2.0 to 20.0 g / 10 min, preferably 3.0 to 16.0 g / 10 min, more preferably 4.0 to 12.0 g / 10 min, and even more preferably 5.0 to 9.0 g / 10 min, as measured according to ASTM D1238 using a temperature of 343° C. and a weight of 2.16 kg.
[0076] In the context of the present invention, the composition more particularly comprises: - at least one PAEK polymer, - 6.0 to 40.0% by weight of talc; - optionally at least one PAES polymer selected from the group of PPSU, PSU, PES and combinations thereof; - optionally at least one nucleating agent, - optionally comprising or consisting of at least one plastics additive;
[0077] The PAES polymer may more particularly be selected from the group of PPSU, PSU and combinations thereof.
[0078] When present, the amount of PAES in the polymer composition preferably ranges from 1.0 to 45.0 wt %, preferably 30.0 to 40.0 wt %, based on the total weight of the PAEK and PAES polymers in the composition.
[0079] In the context of the present invention, the composition more particularly comprises: - at least one PAEK polymer, - 6.0 to 40.0% by weight of talc; - optionally at least one PPSU; - optionally at least one nucleating agent, - optionally comprising or consisting of at least one plastics additive; When present, the amount of PPSU in the polymer composition preferably ranges from 1.0 to 45.0 wt %, preferably 30.0 to 40.0 wt %, based on the total weight of the PAEK and PPSU polymers in the composition.
[0080] In the context of the present invention, the composition more particularly comprises: - at least one PAEK polymer, - 6.0 to 40.0% by weight of talc; - optionally at least one PSU; - optionally at least one nucleating agent, - optionally comprising or consisting of at least one plastics additive; When present, the amount of PSU in the polymer composition preferably ranges from 1.0 to 45.0 wt %, preferably 30.0 to 40.0 wt %, based on the total weight of the PAEK and PSU polymers in the composition.
[0081] The composition may advantageously comprise 55.0-70.0 wt.% PEEK and 45.0-30.0 wt.% PPSU, based on the total weight of PEEK and PPSU in the composition.
[0082] Also, compositions containing PAEK and PAES can be based on the combination of the two PEEKs disclosed above. In other words, for this embodiment, the PAEK polymer is aged at 400° C. for 1,000 s. -1 may correspond to a combination of two PEEKs (PEEK1 and PEEK2) differing in their melt viscosity as measured using a capillary rheometer with a die having dimensions 0.5 mm diameter by 3.175 mm length according to ASTM D3835 at a shear rate of 100 .mu.m. All details and embodiments relating to this combination PEEK1 / PEEK2 apply here too.
[0083] talc The term "talc" refers to either the magnesium silicate mineral or the mineral chlorite (magnesium aluminum silicate), or a mixture of the two, optionally mixed with other minerals such as dolomite and / or magnesite. The term "talc" can also refer to synthetic talc, also known as talcose.
[0084] The talc is advantageously a naturally occurring hydrated magnesium silicate.
[0085] The particles of talc can have any suitable size and / or aspect ratio.
[0086] The talc advantageously exhibits a D50 of less than 10.0 μm, even less than 7.0 μm, even less than 5.0 μm. The D50 is advantageously greater than 0.5 μm, even greater than 1.0 μm. The D50 may be between 0.5 and 10.0 μm, preferably between 7.0 μm, preferably between 0.5 and 5.0 μm, preferably between 1.0 and 5.0 μm.
[0087] The talc advantageously exhibits a D10 greater than 0.1 μm, even greater than 0.2 μm, which may be between 0.1 and 1.0 μm or between 0.2 and 1.0 μm.
[0088] The talc advantageously exhibits a D90 of less than 15.0 μm, even less than 10.0 μm, which may be between 5.0 and 15.0 μm or between 0.2 and 1.0 μm.
[0089] D10, D50 and D90 are determined from the distribution (in volume) of the equivalent spherical diameters of the particles obtained by the sedimentation method. The "Sedigraph III 5120" device supplied by Micromeritics Instruments Corporation, Morcross, Georgia, USA can be used (more details at www.micromeritics.com: http: / / www.micromeritics.com / Repository / Files / SediGraph_5120_Brochure.pdf). This technique and the Sedigraph make it possible to determine the distribution by measuring the speed at which the particles fall under gravity. This technique and the Sedigraph use a narrow, parallel beam of X-rays to directly measure the particle concentration in a liquid medium.
[0090] D10, D50 and D90 have the usual meanings used in the field of statistics and particle size analysis. For example, https: / / www.horiba.com / fileadmin / uploads / Scientific / Documents / PSA / PSA Guidebook.pdf. D50 (median) is defined as the size value corresponding to the 50% cumulative distribution. Similarly, D10 and D90 are defined as the sizes corresponding to the 10% and 90% cumulative distribution, respectively.
[0091] Preferably, the talc may exhibit the following characteristics: - D50 between 1.0 and 5.0 μm; and - D10 higher than 0.1 μm and / or D90 lower than 15.0 μm.
[0092] Nucleating Agent In some embodiments, the composition may also optionally include at least one nucleating agent. The proportion of the nucleating agent is generally less than 2.0% by weight, even less than 1.5% by weight. The nucleating agent is selected from the group consisting of boron nitride, graphite, graphene, mica, and combinations thereof. Graphene is also known as graphite nanoplatelets. The nucleating agent is preferably boron nitride.
[0093] The nucleating agent helps to speed up the crystallization of the molten composition as it is extruded onto the conductor, especially for PAEK and PAES based compositions. This ensures a higher level of crystallinity in the coating - better overall performance of the coating on the wire - e.g. chemical resistance. Additionally, the nucleating agent facilitates increased throughput in the preparation of wire coatings.
[0094] Plastic Additives In some embodiments, the composition may optionally include one or more additives including, but not limited to, colorants (e.g., dyes and / or pigments), UV stabilizers, heat stabilizers, antioxidants, acid scavengers, processing aids, internal and / or external lubricants, flame retardants, smoke suppressants, antistatic agents, antiblocking agents, or any combination thereof.
[0095] When one or more other additives are present, the composition may contain up to 50% by weight, up to 20% by weight, up to 10% by weight, or up to 5% by weight of one or more other additives, based on the total weight of the composition. Most preferably, the proportion of plastic additives is less than 5.0% by weight.
[0096] Viscosity of the composition This composition was melted using a 0.5 × 3.175 mm tungsten carbide die at 400 °C for 1000 s. -1 The melt viscosity, measured in accordance with ASTM D3835 at 120 Pa . s, and at least 130 Pa . s, still at least 150 Pa . s, and at least 200 Pa . s, preferably at least 250 Pa . s, more preferably at least 270 Pa . s. Also, this viscosity is at least 300 Pa . s, more preferably at least 320 Pa . It can be s.
[0097] This composition was melted using a 0.5 × 3.175 mm tungsten carbide die at 400 °C for 1000 s. -1 The melt viscosity, measured according to ASTM D3835 at 0.5° C., is advantageously at most 600 Pa. . s, and a maximum of 580Pa . s, preferably at most 550 Pa . s, more preferably at most 520 Pa . s, most preferably at most 500 Pa . It can be s.
[0098] Compositions having a melt viscosity in the range of 250-520 Pa.s, preferably between 250-500 Pa.s, preferably between 300-500 Pa.s, or between 300-400 Pas or more preferably between 300-360 Pas, have surprisingly been found to provide good adhesion to conductors.
[0099] 10000s -1 Viscosity at 400°C and 10,000s using a 0.5 x 3.175 mm tungsten carbide die: -1 The melt viscosity, measured according to ASTM D3835 at 25° C., is at least 50 Pas, and preferably at least 90 Pas. . s, and at least 100 Pa . This composition can be melted at 400°C and 10,000 s using a 0.5 x 3.175 mm tungsten carbide die. -1 The melt viscosity measured according to ASTM D3835 at 130 Pa . s, and a maximum of 120 Pa . It can be s.
[0100] 100s -1 Viscosity at 400°C and 100s using a 0.5 x 3.175 mm tungsten carbide die. -1 The melt viscosity, measured according to ASTM D3835 at 200 Pa . s, and at least 400 Pa . This composition can be melted using a 0.5×3.175 mm tungsten carbide die at 400° C. for 100 s. -1 The melt viscosity measured according to ASTM D3835 at 1000 Pa . s, and even a maximum of 900 Pa . It can be s.
[0101] Viscosity ratio r: It has also been discovered that a good balance of properties is obtained when the viscosity ratio r is between 5.0 and 10.0, and r is the viscosity ratio at 400°C and 100s. -1The melt viscosity at 400℃ and 10000s -1 The ratio r is defined as the ratio of the melt viscosity at r divided by the melt viscosity at r. The ratio r is preferably at least 6.0. The ratio r is preferably at most 9.0 or at most 8.0.
[0102] Also, the ratio r may preferably be between 5.0 and 9.0, preferably between 6.0 and 8.0.
[0103] Tensile elongation at break The composition advantageously exhibits a tensile elongation at break of at least 10.0%, preferably at least 13.0%, more preferably at least 16.0%, and even more preferably at least 20.0%, when measured according to ASTM D638 (3.2 mm thick Type I specimen, 50 mm / min).
[0104] The tensile elongation at break is usually at most 30.0%, more preferably at most 15.0%.
[0105] Method for preparing the composition The composition can be produced by any known melt mixing process suitable for preparing thermoplastic compositions or compounds. The process is conveniently carried out in a melt mixing device. Any melt mixing device known to those skilled in the art of preparing polymer compositions by melt mixing can be used.
[0106] Suitable melt mixing equipment can be selected, for example, from the list consisting of kneaders, Banbury mixers, single screw extruders and twin screw extruders. A convenient melt mixing equipment is a single screw extruder or a twin screw extruder. A convenient melt mixing equipment can be the equipment used in the examples.
[0107] The design of the compounding screw (e.g., the pitch and width of the screw, the clearance, the length) and the operating conditions of the extruder are preferably and advantageously selected to provide sufficient heat and mechanical energy to fully melt the polymeric components of the composition and to obtain a homogeneous distribution of the various components of the composition. At the exit of the extruder, the strand extrudate of the composition can be chopped, for example by a rotating cutting knife, after a certain cooling time on a conveyor by water spray. The composition can be in the form of a powder or in the form of pellets. The latter form is preferred as it is more convenient to use.
[0108] The preparation methods in the examples can be advantageously used to prepare the compositions of the present invention.
[0109] Insulation layer In some embodiments, the insulating layer comprises the composition detailed above.
[0110] The thickness of the insulating layer is typically less than 200 μm, even less than 180 μm. The thickness of the insulating layer is preferably greater than or equal to 5 μm, more preferably greater than 15 μm.
[0111] The compositions disclosed in the present invention allow for increased thickness while maintaining a good compromise of properties. The thickness can be increased up to 300.0 μm. Thus, the thickness of the insulating layer can generally be between 5.0 and 300.0 μm.
[0112] The composition provides sufficient insulation of the conductors, and because the composition is crystalline, it also provides good chemical and mechanical resistance.
[0113] Electrical conductor The conductors can be formed from a wide variety of suitable materials and / or combinations of materials. For example, the conductors can be formed from copper, aluminum, annealed copper, oxygen-free copper, silver-plated copper, nickel-plated copper, copper-clad aluminum, silver, gold, conductive alloys, bimetals, carbon nanotubes, or any other suitable electrically conductive material. Typically, the conductors are copper-based conductors. Typically, the conductors consist essentially of copper.
[0114] Additionally, the conductor can be formed to have any suitable size and / or cross-sectional shape. The conductor can have a circular or round cross-sectional shape, or it can be formed to have a square, rectangular, elliptical or oval shape, or any other suitable cross-sectional shape.
[0115] The conductors can have any suitable dimensions, such as any suitable gauge, diameter, height, width, cross-sectional area, etc.
[0116] The wire may comprise more than one insulating layer and / or additional layers, provided that at least one insulating layer as defined above is in direct contact with the surface of the conductor. It has been found that the composition of the insulating layer of the invention makes it possible to obtain good adhesion of the insulating layer to the conductor without any adhesive layer and / or enamel. The wire of the invention therefore does not comprise any adhesive and / or enamel layer between the conductor and the composition.
[0117] When two or more insulating layers are used, they may have the same or different compositions.
[0118] In certain embodiments, in addition to the insulating layer or layers, the wire may include one or more suitable wraps or tapes. For example, a polymeric tape may be wrapped around the conductor and the insulating layer. In other embodiments, the wire may include one or more layers of an extruded material having a composition different from that of the insulating layer.
[0119] Method for manufacturing a wire A further object of the invention is a method for manufacturing the wire.
[0120] In certain embodiments, the conductors may be formed in conjunction with the application of the insulating layer. In other embodiments, the conductors having the desired dimensions may be preformed or obtained from an external source. The insulating layer may then be applied or otherwise formed over the conductors.
[0121] In certain embodiments, the insulating layer is extruded and the extruded insulation is formed directly around the conductor. Known extrusion coating techniques can be used to form the insulating layer directly around the conductor. The extruded insulating layer can be formed to have any suitable thickness desired. The thickness of the extruded insulating layer is selected to be thin enough to allow relatively dense packing of the resulting wires, for example in an electric motor, but thick enough to provide suitable insulation and / or mechanical resistance. The conditions used in the examples are applicable and can be used for copper, but can also be used for any other metal.
[0122] In an alternative embodiment, the insulating layer can be extruded in the form of a film or tape and then applied to the conductor, for example, the insulating layer can be wrapped around the conductor and then subjected to a heat treatment to consolidate the structure.
[0123] In other embodiments, one or more suitable surface modification treatments can be utilized on the conductor to promote adhesion with the insulating layer. For example, the surface of the conductor can be roughened. Roughening can include etching (e.g., chemical or laser etching), mechanical grinding, or any combination thereof. Examples of alternative and / or additional surface modification treatments include, but are not limited to, plasma treatment, ultraviolet light ("UV") treatment, corona discharge treatment, and / or gas flame treatment. The surface treatment can alter the topography of the conductor and / or form functional groups on the surface of the conductor that enhance or promote bonding of the subsequently formed insulating layer. As a result, the surface treatment can reduce delamination of the interlayer.
[0124] Wire The wire of the present invention can be used in a wide variety of applications, such as in a wide variety of electrical machines and devices, such as inverter drive motors, motor starter generators, transformers, and the like.
[0125] The electric machine may also be an electric motor, a synchronous generator or a generator. This electric machine comprises a stator and a rotor. The stator comprises a metal core comprising the wire of the invention. The invention extends to a stator incorporating the wire of the invention.
[0126] The wire may have a circular cross-section.
[0127] The wires can also have a non-circular cross-section. For example, the wires can have a square, rectangular, elliptical or oval cross-section. The wires can also have a cross-section that is generally square, rectangular, elliptical or oval.
[0128] More particularly, the wire may exhibit a cross-section comprising a first outwardly facing surface and a second outwardly facing surface, wherein said first and second surfaces are preferably substantially planar and preferably said first and second surfaces face in opposite directions but extend substantially parallel to one another.
[0129] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that certain terms may be unclear, the statements herein shall control.
[0130] The invention will be described in more detail below by reference to examples, but the invention is not limited to these examples. EXAMPLES
[0131] raw materials: 400℃ for 1,000 seconds -1 420 Pa when measured using a capillary rheometer with a die having dimensions of 0.5 mm diameter x 3.175 mm length according to ASTM D3835. . KetaSpire® KT-820 high viscosity grade PEEK having a melt viscosity of 1.0 s.
[0132] KetaSpire® KT-880 low viscosity grade PEEK having a melt viscosity of 150 Pa-s when measured using the same conditions described above.
[0133] Radel® R-5800NT: A PPSU available from Solvay Specialty Polymers. This grade exhibits an MFR of 25 g / 10 min when measured according to ASTM D1238 using a temperature of 365° C. and a 5.0 kg weight.
[0134] Talc: Mistron® Vapor from Imerys Performance Additives; median particle size D50 of approximately 2 μm. D10=0.5 μm and D90=7.4 μm. These values are obtained by Sedigraph.
[0135] Hostanox P-EPQ is an antioxidant supplied by Clariant Corp.
[0136] Preparation of Example Compositions All compositions were prepared by first tumble blending the polymer and talc powders to be blended in the desired composition ratio for approximately 20 minutes, followed by melt compounding using a 26 mm Coperion® co-rotating partially intermeshing twin screw extruder with a L / D ratio of 48:1. The extruder had 12 barrel sections with a temperature profile setting of 350°C for barrel sections 2-12 and a pinhole die. The melt temperature recorded for the extrudate as it exited the die ranged from 370-390°C for all compositions. The extruder feed consisted of the resin components gravimetrically metered into the extruder feed hopper, while the desired fillers were also metered into barrel section 7 using a gravimetric feeder in the ratios corresponding to Table 1. The extruder was operated at a total throughput of 35 lb / hr (15.9 kg / hr) and a screw speed of 200 rpm, and the extruder torque reading was maintained at approximately 75% during compounding of all compositions. A vacuum discharge having a vacuum level >25 in Hg was applied at barrel section 10 during compounding to strip the compound of moisture and any possible residual volatiles. The extrudate from each run was stranded, cooled in a water trough, and then pelletized into pellets approximately 2.7 mm in diameter and 3.0 mm in length.
[0137] Preparation of test films The prepared pellets of the example compositions were processed into films with a thickness of 130-150 μm and a width of 8-9 cm using a single screw extruder from OCS Optical Control Systems, GmbH. The extruder had a single stage non-vented screw with a diameter of 20 mm and an L / D ratio of 30. The extruder was equipped with a 125 mm wide film die with a gap thickness of 0.5 mm. The barrel of the extruder had four heating sections, which were operated from rear to front at set temperatures of about 350° C., 385° C., 390° C., and 395° C., respectively. The film die was set at a temperature of 395° C. The films were stretched and formed with two chill rolls, set at 240 and 245° C. for the first and second rolls, respectively. The film and compound throughput was determined by the film take-up speed of about 1 m / min, and the extruder was operated at a screw speed of 17 rpm.
[0138] Wire sample preparation Selected formulations were extruded onto copper wire for testing. Uncoated round copper wire, size AWG12, was coated with the polymer using an Entwistle 1.5 inch (3.8 cm) extruder and a Unitek center fixed crosshead. The wire was cleaned and then preheated to the desired temperature between 300-450°C using a Zumbach induction heater before being extruded onto the wire. A pressure tool with a 0.082 inch (0.21 cm) tip and a 0.090 inch (0.23 cm) die was used. The line was run at 12-37 m / min and a wall thickness of 0.005 inch (0.12 mm) was targeted. The wire was allowed to cool in ambient air before being collected for testing.
[0139] The insulation layer of the wire samples had a thickness of 125 μm.
[0140] test The following ASTM test methods were used in evaluating all compositions: D638: Tensile properties - strength, modulus and elongation at break D3835: Evaluation of melt viscosity by capillary rheometry using a 0.5 x 3.175 mm tungsten carbide die at a temperature of 400°C.
[0141] Injection molding was performed with the example formulations to produce 0.125 inch thick ASTM tensile and flexural specimens for mechanical property testing. Type I tensile ASTM specimens and 5 inch x 0.5 inch x 0.125 inch flexural specimens were injection molded using PEEK injection molding guidelines provided by the supplier.
[0142] Peel Force Test A specialized tool was designed and machined to measure the strip force required to remove the coating from the wire, as shown below. A 3 inch (7.6 cm) length of wire was used for the test. A 1.5 inch (3.8 cm) piece of wire was hand stripped of its coating material and inserted into a 0.083 inch (2.1 mm) diameter hole in a drill bushing. The drill bushing was inserted into the tool attached to an Instron Model 5565 and the uncoated portion of the wire was clamped in the upper grips. The wire was pulled at a rate of 0.1 inch / min (2.5 mm / min), the load on the grips was measured, and the maximum load observed was recorded as the strip force of the sample. The results are summarized in Table 1.
[0143] Peel Strength Test Peel tests were performed using extruded films of each composition to determine the adhesion of the composition to metal substrates. For each test specimen, a 5×10 cm metal sheet of 0.024 inch (0.61 mm) thickness composed of either copper or stainless steel was used as the substrate. Prior to testing, the metal sheet was cleaned with acetone to remove any residual grease or oil from the surface. The polymer film to be tested was cut into a 3×1.5 inch rectangle with the long edge perpendicular to the extrusion direction. Aluminum foil was folded over approximately 0.5 inch (12.7 mm) of the polymer film on one of the short ends. The upper and lower platens of the melt press were preheated to 400° C. For each test, the polymer film was placed on the metal substrate, the platens were spaced approximately 5 cm apart, and the metal / polymer assembly was placed directly on the lower platen adjacent to a preheated 3 / 16 inch (0.5 cm) thick stainless steel plate. The platens were then closed so that the gap between the upper and lower platens was 3 / 16 inch (0.5 cm) and the assembly remained in place for 2 minutes. The platens were then opened to a 10 cm wide gap and the assembly was allowed to rest on the lower platen for 1 minute. After a total of 3 minutes on the press, the assembly was transferred to a 3 / 16 inch (0.5 cm) thick stainless steel hot plate and the plates were transferred to an ambient temperature cooling press.
[0144] The 90° peel test was performed on an Instron Model 5565 with a jaw face grip on the upper attachment and a sliding platform on the lower attachment. Prior to the peel test, the film adhered to the metal sheet was scored along each long edge to remove edge effects and leave a film section with a width of at least 0.5 inches (12.7 mm) that was peeled from the metal substrate. The film was peeled from the substrate at a rate of 0.1 inches / minute (2.5 mm / minute) and the load was recorded and normalized for the sample width that was scored.
[0145] The results are summarized in Table 1, where the symbols have the following meanings: (---): Peeled off before scoring (--+): Partially peeled off before scoring (-++): Peeled off when scored (+++): Torn Here, the melt viscosity is given in Pas.
[0146] [Table 1]
[0147] Adhesion to smooth metal substrates is improved by the addition of talc to compositions containing only PEEK or low amounts of talc. Adhesion is at a good level even without an adhesive layer between the metal substrate and the thermoplastic layer.
[0148] The peel strength data shows that at the same loading of talc, adhesion to the wire increases with increasing viscosity of the formulation.
[0149] The wires of the examples exhibit strong adhesion, as shown by the results in Table I. As can also be seen, the wires of Examples E7-E10 exhibit a balance of properties.
Claims
1. a conductor; at least one insulating layer formed around and in direct contact with said conductor, said insulating layer comprising or made from a composition comprising at least one polyaryletherketone polymer and 6.0 to 40.0% by weight of talc relative to the total weight of the composition, and said composition being aged at 400° C. and 1000 s -1 The wire has a melt viscosity of at least 120 Pa·s as measured in accordance with ASTM D3835 at 100° C.
2. The composition, at least one polyaryletherketone polymer (PAEK polymer), which is a combination of two PEEKs (PEEK1 and PEEK2) differing in melt viscosity measured using a capillary rheometer with a die having dimensions of 0.5 mm diameter by 3.175 mm length according to ASTM D3835 at a shear rate of 1,000 s at 400° C., - 6.0 to 40.0% by weight of talc, - optionally at least one polyarylethersulfone polymer (PAES polymer), optionally at least one nucleating agent, preferably boron nitride, - optionally with at least one plastic additive; 2. The wire of claim 1, comprising or consisting of:
3. The composition, at least one polyaryletherketone polymer (PAEK polymer), - 6.0 to 40.0% by weight of talc, at least one polyarylethersulfone polymer (PAES polymer), optionally at least one nucleating agent, preferably boron nitride, - optionally with at least one plastic additive; 2. The wire of claim 1, comprising or consisting of:
4. The polyaryl ether ketone polymer has the formula (JA) to (JQ): 【Chemistry 1】 【Chemistry 2】 (In the formula, each of -R' is equal to or different from one another and is selected from the group consisting of halogen, alkyl, alkenyl, alkynyl, aryl, ether, thioether, carboxylic acid, ester, amide, imide, alkali or alkaline earth metal sulfonate, alkyl sulfonate, alkali or alkaline earth metal phosphonate, alkyl phosphonate, amine and quaternary ammonium; -j' is zero or an integer from 0 to 4, preferably j' is zero), PAEK 4. The wire according to claim 1, further comprising:
5. The polyaryl ether ketone polymer has the following formulae (J'-A) to (J'-O): 【Chemistry 3】 【Chemistry 4】 At least 50% by weight of repeating units (R PAEK 5. The wire according to claim 1 , comprising:
6. A wire according to any one of claims 1 to 5, wherein the polyaryletherketone polymer is a polyetheretherketone ("PEEK") polymer.
7. The polyarylethersulfone polymer (PAES polymer) is selected from the group consisting of PPSU, PES, and PSU, which are: at least 60 mol %, or at least 70 mol %, or at least 80 mol %, or at least 90 mol %, or at least 95 mol %, or at least 99 mol % More mol % of each of the formulae (B1), (B2), and (B3): 【Chemistry 5】 (wherein d=e=f=0) PAES 7. The wire according to claim 2, further comprising:
8. The melt flow rate (MFR) of the PPSU, measured according to ASTM D1238 using a temperature of -365°C and a weight of 5.0 kg, is in the range of 5.0 to 45.0 g / 10 min, preferably 10.0 to 40.0 g / 10 min, more preferably 15.0 to 35.0 g / 10 min, and even more preferably 20.0 to 30.0 g / 10 min; or 8. A wire according to claim 7, wherein the melt flow rate (MFR) of said PSU, measured according to ASTM D1238 using a temperature of -343°C and a weight of 2.16 kg, is in the range of 2.0 to 20.0 g / 10 min, preferably 3.0 to 16.0 g / 10 min, more preferably 4.0 to 12.0 g / 10 min and even more preferably 5.0 to 9.0 g / 10 min.
9. 9. A wire according to any one of claims 2 to 8, wherein the amount of PAES polymer in the polymer composition is in the range of 1.0 to 45.0 wt.%, preferably 30.0 to 40.0 wt.%, based on the total weight of the PAEK and the PAES polymer in the composition.
10. 10. Wire according to any one of the preceding claims, wherein said talc exhibits a D50 comprised between 0.5 and 10.0 μm, D50 being the median of the distribution (in volume) of the equivalent spherical diameter of the particles obtained by the sedimentation method.
11. PEEK1 exhibits a viscosity of more than 300 Pa·s, and this viscosity is 1,000 s at 400°C. -1 and / or PEEK2 exhibits a viscosity lower than 200 Pa·s, which viscosity is measured using a capillary rheometer with a die having dimensions 0.5 mm diameter×3.175 mm length according to ASTM D3835 at a shear rate of 1,000 s −1 at 400° C., and / or the weight ratio PEEK1 / PEEK2 is between 50 / 50 and 70 / 30.
12. The melt viscosity of the composition was measured at 400° C. and 1000 s using a capillary rheometer having a die with dimensions of 0.5 mm diameter by 3.175 mm length. -1 12. A wire according to any one of the preceding claims, having a viscosity of 250 to 500 Pa s when measured according to ASTM D3835 at 1000 psi.
13. The composition exhibits a viscosity ratio r between 5.0 and 10.0, or a ratio r of at least 6.0, and r is within the range of 100 s -1 The melt viscosity at 10,000 s -1 13. The wire according to any one of claims 1 to 12, wherein the melt viscosity at 400°C is defined as the ratio of the melt viscosity at 400°C divided by the melt viscosity at 20°C, both viscosities being measured according to ASTM D3835 using a capillary rheometer with a die having dimensions of 0.5 mm diameter by 3.175 mm length.
14. Wire according to any one of the preceding claims, wherein the composition comprises from 10.0 to 26.0% by weight of talc or the proportion of talc is between 6.3 and 8.5% by weight.
15. 15. Wire according to any one of the preceding claims, wherein the composition exhibits a tensile elongation at break, measured according to ASTM D638 (3.2 mm thick Type I specimen, 50 mm / min), of at least 10.0%, preferably at least 13.0%, more preferably at least 16.0%, and even more preferably at least 20.0%.
16. A wire according to any one of the preceding claims which is a magnet wire.
17. A method for manufacturing a wire according to any one of claims 1 to 16, comprising the step of extruding a composition to form the insulating layer, the composition comprising at least one polyaryletherketone polymer and 6 to 40 wt. % of talc, based on the total weight of the composition, and extruding the composition at 400°C and 1000s. -1 having a melt viscosity of at least 120 Pa·s as measured according to ASTM D3835 at .
18. The method of claim 17 , wherein the insulating layer is formed directly on the conductor by extrusion coating.
19. 20. The method of claim 17, wherein the insulating layer is extruded in the form of a tape, the method further comprising the steps of providing a conductor, wrapping the insulating layer around the conductor, and applying heat to adhere the insulating layer to the conductor.
20. An electric machine comprising at least one wire according to any one of the preceding claims.
21. A stator incorporating a wire according to any preceding claim.
22. Use of the wire according to any one of claims 1 to 16 in electrical machines and devices such as inverter drive motors, motor starter generators, transformers etc.